The Influence of Live Commerce Platforms on Generation Z Impulse Buying in Java Island: Use and Gratification Theory Approach - Dominikus Kresna Widya Purnomo; Werner R. Murhadi (Sekolah Tinggi Manajemen IPMI, 2025)
This study explored the influence of live commerce platforms on impulsive buying in Java Island using the Use and Gratification Theory approach. The focus of the study was to analyze how variables such as perceived interactivity, perceived information usefulness, perceived affective gratification, perceived enjoyment, and the influence of social media affected positive attitudes towards live commerce and impulsive buying behavior. This study also compared the differences in results between previous studies related to hedonic browsing and utilitarian browsing. Java Island was chosen as the research location because it has the highest internet penetration rate in Indonesia, a significant contribution to online shopping, and the largest number of e-commerce entrepreneurs. A quantitative approach was used in this study with a survey technique through purposive sampling. Data were collected from 359 respondents who had used the live commerce platform at least once a month. The results showed that out of 10 hypotheses, perceived affective gratification and perceived enjoyment influenced attitudes towards live streaming, but not perceived interactivity and perceived information usefulness. Furthermore, attitude towards live streaming influenced hedonic and utilitarian browsing, but did not influence impulsive buying. Other hypotheses that influenced impulsive buying were hedonic browsing and EWOM, while utilitarian browsing was not supported.